Respiratory Parameters in Elite Finn-Class Sailors - Luka Pezelj; Boris Milavic; Marko Erceg (Montenegrin Sports Academy, 2019)
Spirometry is an essential test for assessing the state of the respiratory system. It provides the measurement of the ventilation volumes and fl ows expressed in absolute and relative values. Among elite athletes, the values of ventilation parameters are usually higher than the norm; therefore the interpretation of individual results of elite athletes in relation to the general healthy population is not advisable. Th is study aimed to determine the respiratory characteristics of elite sailors in the Olympic Finn class, and the diff erences between more successful and less successful sailors according to the criterion of sport effi cacy. Th e study included 33 sailors of the Olympic Finn class who participated at the 2015 Finn European Championship. Absolute values of spirometry parameters of elite Finn sailors (FVC-Forced-vital-capacity 5.96±0.79; FEV1-Forced-expiratoryvolume-in-1-second 5.10±0.63; FEV1/FVC%-Forced-expiratory-volume-in-1-second/Forced-vital-capacity 86.10±6.38; MVV-Maximum-voluntary-ventilation 190.94±32.64) are higher than the spirometry values of most other athletes. Relative values of spirometry parameters of elite Finn sailors (FVC% 101.24±14.21; FEV1% 102.53±12.09; FEV1/FVC%% 102.00±7.94; MVV% 96.77±18.59) are within the ranges of most elite athletes. Elite sailors can be considered healthy in terms of ventilation, and sailing as a sports activity can be considered benefi cial for the ventilatory function of the lungs. More successful sailors had higher mean values of absolute and relative ventilation parameters of FVC, FEV1, and MVV, whereas signifi cant diff erences were determined in the variables of MVV. Th e diff erences between more successful and less successful sailors in the MVV and MVV% variables could be interpreted precisely by the state of respiratory muscles.